Impact of Frontline Demonstrations on Jute - Rajendra R. Chapke, (Indian Journal of Extension Education, 2022)
In order to increase production and productivity of jute by adopting improved production technologies, serveral frontline demonstrations (FLDs) on jute with package technologies were conducted by Central Research Institute for jute and Allied Fibres (CRIJAF), Barrackpore West Bengal. A study on impact of the demonstrations on the farmers' behaviour was conducted. Results of the study revealed that demonstrated technologies increased the fibre yield of jute by 4.45 q ha-1 over the farmer's practice (25.10 q ha-1), the post-demonstration yield was 29.55 q ha-1 as the farmers adopted many components of the technology package that were used in demonstrations. Economic surplus from increased production of jute fibre by about 4.45 q ha-1 provided additional Rs. 5570 ha-1 to the farmers. The results further indicated that addition income that accrued due to increased harvest of jute by adopting improved practices was utilized by the farmers by increasing expenditure by about 50 per cent, on food, health care of the family members, education of children, and purchase of farm implements or essentials or essential items including attending social and entertainment programmes. Impact of the demonstrated technologies to increase fibre yield of jute by contact farmers up to 3 q ha-1 in nearby villages within radius to three to seven km distance from the adopted villages was also found. A definite impact of the FLDs was thus observed.